How the War on Terror Is Transforming Private U.S. Law - Maryam Jamshidi (Washington University Law Review, 2018)
In thinking about the War on Terror’s impact on U.S. law, what most likely comes to mind are its corrosive effects on public law, including criminal law, immigration, and constitutional law. What is less appreciated is whether and how the fight against terrorism has also impacted private law. As this Article demonstrates, the War on Terror has had a negative influence on private law, specifically on torts, where it has upended long-standing norms, much as it has done in the public law context. Case law construing the private right of action under the Antiterrorism Act of 1992, 18 U.S.C. § 2333(a) (“Section 2333”), shines the brightest light on this trend. Using Section 2333, private individuals can bring civil suits against third-parties for injuries purportedly resulting from violence committed by terrorist groups. In deciding these cases, which sound in intentional torts, many courts have treated Section 2333 as a critical component of U.S. counterterrorism efforts. This marriage of tort law and national security has transformed Section 2333 into anything but the traditional tort Congress intended it to be. In the process, a line of jurisprudence has developed under the statute, which carries negative implications for the discipline of torts writ large, reinforces the War on Terror’s ideologically-infused narratives about terrorism itself, and ensnares defendants with little to no meaningful connection with terrorism or terrorist groups. These consequences, which have largely gone unnoticed by both tort scholars and critics of U.S. counterterrorism efforts, are important ones. They highlight the ways America’s never-ending war has not only undermined public, but also private, law, and underscore how torts, in particular, have helped perpetuate the political ideology at the root of that battle. This Article seeks to uncover and explain these trends, for the first time, and offer some preliminary solutions.
Keywords: War on Terror; 18 U.S.C. § 2333(a); Section 2333; counterterrorism; private law; terrorism; tort law; public law; jurisprudence; Antiterrorism Act of 1992; ATA; never-ending war; national security; intentional tort; Limitless Liability; Scienter Requirement; civil material support statute; Terrorism Civil Remedy; Causation Requirement